Teaching Non-Italian Students: Italian Adaptation of the Questionnaire on Teachers' Perspectives - Ceyda Sensin; Guido Benvenuto; Emiliane Rubat du Mérac (LED Edizioni Universitarie, 2020)
The survey of teachers' perspectives on the teaching of refugees and immigrant pupils by Kurbegovic (2016) is used to evaluate five dimensions of teachers' self-perception: Selfefficacy, Implementation Practices, Cultural Competence, Competence/Preparation and Student Needs. The present study is aimed at analysing the self-awareness of primary school teachers of the teaching of refugee and immigrant students in Italy. The survey of Kurbegovic within its 30 items (Cronbach's Alpha = .86) was conducted on a sample of 190 teachers who teach in primary schools in Rome. After removing 2 items that are cross loading, the exploratory factor analysis (Maximum likelihood method with Oblimin rotation) confirms a five-factor structure and shows a good construct validity and reliability. Current research reveals that the survey of teachers' perspectives on refugee and immigrant populations is appropriately adapted to assess Italian primary school teachers' views. This tool demonstrates its usefulness not only for research but also for pedagogical practice and can help to create an inclusive classroom environment that provide students with equal access to the curriculum and learning experiences.